2018
DOI: 10.1016/j.vph.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin and-L-arginine combination improves umbilical artery blood flow and neonatal outcomes in dichorionic twin pregnancies through an nitric oxide-dependent vasorelaxant effect

Abstract: The increase in fetal and neonatal morbidity and mortality associated with twin pregnancies correlates with an increased risk of preterm delivery, low birth weight, and intrauterine growth restriction (IUGR). Although the pathogenesis of IUGR is unclear and thus management remains a major challenge, feto-placental blood vessels are compromised, and altered umbilical blood flow is observed. In this pilot observational study we investigated the effects of pravastatin plus l-arginine on umbilical artery (umb art)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
8
1
Order By: Relevance
“…6,21,26 The severity of Doppler findings and its progression over time is also related to poorer pregnancy prognosis. 21,27 In previous studies, pravastatin proved to induce better feto-placental circulation assessed by Doppler 16,28 ; however, in the present study, no significant improvement in Doppler parameters could be observed.…”
Section: Discussioncontrasting
confidence: 67%
“…6,21,26 The severity of Doppler findings and its progression over time is also related to poorer pregnancy prognosis. 21,27 In previous studies, pravastatin proved to induce better feto-placental circulation assessed by Doppler 16,28 ; however, in the present study, no significant improvement in Doppler parameters could be observed.…”
Section: Discussioncontrasting
confidence: 67%
“…Consequently, increases in placental NO caused by pravastatin resulted in adequate blood supply into foeto‐maternal interface; thus, NO allowed foeto‐placental development because it protected against unappropriated remodelling of the maternal uteroplacental vasculature induced by hypertensive pregnancy and that caused foeto‐placental growth restriction . Therefore, we believe that the effects of NO signalling may be due to their general effects on angiogenesis, endothelial cell growth, endothelium‐dependent vasodilation, vasculogenesis and placental development …”
Section: Discussionmentioning
confidence: 99%
“…Pravastatin has shown protective effects during foetal development in gestational hypertension in animals . In addition, in humans, pravastatin effects involved augmented levels of vasodilator NO that prevented the onset of pre‐eclampsia and attenuated the intrauterine growth restriction . However, these cholesterol‐independent mechanisms due to pravastatin have not yet been fully clarified in hypertensive disorders of pregnancy correlated with foetal growth restriction.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that statins could be a promising therapeutic or preventive strategy for placental insufficiency [8,9]. Significant clinical benefits and improvement in the angiogenic profile have been reported in patients with early-onset preeclampsia [10] and umbilical artery flow in twin pregnancies with discordant fetal growth seems to improve after pravastatin is started [11]; however, no previous studies reported the effect of pravastatin on the uterine artery Doppler and angiogenic factors of FGR single pregnancies in humans.…”
Section: Introductionmentioning
confidence: 99%